Rancang Bangun Aplikasi Customer Relationship Management pada PT Goresan Pena Runcing - Willy Sutikno Mustika Wijaya; Farizi Ilham; Rafli Hardiansyah; Arya Bintang (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
The rapid development of information technology encourages companies to improve customer service quality through integrated information systems. PT Goresan Pena Runcing, a company engaged in business legality services, still faces challenges in customer data management, communication history recording, service monitoring, and customer follow-up processes that are handled manually. These conditions reduce operational efficiency and may affect service quality. This study aims to design and develop a web based Customer Relationship Management (CRM) application capable of managing customer data centrally, recording communication activities, monitoring service progress, and generating reports automatically. The system was developed using the Waterfall method, which consists of requirements analysis, system design, implementation, testing, and maintenance stages. The results indicate that the proposed CRM application can improve operational efficiency, simplify customer data management, accelerate service monitoring, and support data-driven decision-making processes. The implementation of this system is expected to enhance customer satisfaction and strengthen the company's competitiveness in the business legality service sector.